Parfit on Personal Identity: A Psychological Study of the Immigrants in Samuel Selvon’s The Lonely Londoners - Hama, Asst. Prof. Dr. Bakhtiar Sabir; Mohammed, Dlnya Abdalla (Sulaimani Journal for Humanities, 2023)
This study introduces a psychological analysis of the immigrants in Selvon’s The Lonely Londoners through the lens of Derek Parfit’s notion of identity. It examines the psychological predicaments of West Indian immigrants who migrated to London in the 1950s searching for a better life, but were subjected to racial discrimination, alienation, and sufferings, resulting in the loss of their own identities before gaining a new one. The immigrants find themselves confused and psychologically disturbed in the harsh and cold British society. Despite the racial abuse and discrimination metered against them, immigrants slowly coped with London’s life by adopting a new identity. The researcher has used Parfit's perception of identity to examine the psychological sufferings that immigrants faced in The Lonely Londoners. Through the characters, Selvon presents various colonial concepts, such as nostalgia, racism, and marginalization that impact immigrant’s mental states and identities.
Keywords: Keywords Self identity; Psychological connectedness; Psychological continuity; Parfit's theory